Association between BANK1 polymorphisms and susceptibility to autoimmune diseases: A meta-analysis - Bae, S-C.; Lee, Y. H. (Cellular and Molecular Biology, 2017)
This study aimed to explore whether BANK1 polymorphisms are associated with susceptibility to autoimmune diseases. We conducted a meta-analysis on the associations between the BANK1 rs10516487, rs3733197, and rs17266594 polymorphisms and autoimmune diseases. Twenty-two articles with a total of 22,684 patients and 36,437 controls were included in the meta-analysis. Meta-analysis revealed a significant association between autoimmune diseases and the BANK1 rs10516487 T allele (OR = 1.161, 95% CI = 1.092–1.275, p = 1.9 í— 10-6, heterogeneity p < 0.001). The analysis also revealed an association between autoimmune diseases and the BANK1 rs3733197 A allele (OR = 1.178, 95% CI = 1.105–1.256, p = 4.5 í— 10-7, heterogeneity p = 0.002) and the rs17266594 T allele (OR = 1.189, 95% CI = 1.073–1.315, p = 0.001, heterogeneity p < 0.001). Meta-analysis by autoimmune disease type revealed an association between both systemic lupus erythematosus and systemic sclerosis and the BANK1 rs10516487 T allele (OR = 1.294, 95% CI = 1.232–1.360, p < 1.0 í— 10-8, heterogeneity p = 0.556; OR = 1.102, 95% CI = 1.027–1.183, p = 0.017, heterogeneity p = 0.048). However, meta-analysis failed to indicate an association between the BANK1 rs10516487 T allele and rheumatoid arthritis (RA; OR = 1.006, 95% CI = 1.956–1.058, p = 0.819). This meta-analysis demonstrates that BANK1 rs10516487, rs3733197, and rs17266594 polymorphisms are associated with susceptibility to autoimmune diseases.